Implementation of simple additive weighting (SAW) in determining nutrition in toddlers - Amriana, Amriana; Ardiansyah, R; Wirdayanti, Wirdayanti; Masykur, M (Applied Engineering and Technology, 2023)
The stunting or malnutrition in toddlers are the main problems facing society today[1]. Also, the fact that these young children experience lack of adequate nourishment in Indonesia is quite indisputable. Handling nutritional problems is closely related to the strategy of a nation to create healthy, intelligent and productive human resources. Efforts to improve quality human resources begin with how to manage children's growth as part of a family with good nutrition and care For this reason, this study takes part in supporting the alleviation of cases of malnutrition by using the Simple Additive Weighting (SAW) Method which is used to find the optimal alternative from a number of alternative criteria. The basic concept of SAW is to find the weighted sum of the performance ratings for each alternative across all attributes[2]. The SAW method requires a decision matrix normalization process (X) to a scale that can be compared with all alternative ratings[3]. The SAW method recognizes 2 attributes, namely the benefit criteria and the cost criteria. The method used was Simple Additive Weighting (SAW) which consists of 2 criteria, namely Height (TB) and Weight (BW) according to age for toddlers. The calculation accuracy of this application is 90% of the tested data